Drama education and children's philosophy in practice - Kazinczy, Viktória (Acta Cultura et Paedagogicae, 2026)
Integrating children's philosophy into drama pedagogy is an innovative pedagogical approach that integrates two separate but complementary fields. Drama pedagogy in itself is a tool for developing children's creativity, emotional intelligence and social skills, but the incorporation of children's philosophy methodology can bring additional critical thinking, reflective and ethical dimensions to the learning process. The relationship between children's philosophy and drama pedagogy is therefore an exciting and closely collaborative one, as both aim to develop children's thinking skills, but through different methods. Both methods aim to increase shared thinking, dialogue and empathy, so that when used together, children can develop more complex, deeper thinking, better self-expression and social relationships. Philosophical questions and discussions deepen the lessons learned from dramatic situations and provide children with the opportunity to reflect more consciously and deeply on the world and their own actions. This complex approach develops children's social, emotional and thinking skills and helps them develop an ethical awareness.